2018
DOI: 10.1371/journal.pone.0198730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of family therapeutic interventions in the prevention and treatment of perinatal depression: A systematic review and meta-analysis

Abstract: BackgroundFamily therapy is a potential strategy to increase family support for those suffering from perinatal depression. Family therapeutic interventions for this population typically target depressed women and their adult family members to improve family functioning and reduce depressive symptoms.ObjectiveThis systematic review and meta-analysis is a synthesis of the current evidence on the usefulness of family therapy interventions in the prevention and treatment of perinatal depression and impacts on mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…There is a scarcity of research on the use of HIPAA-compliant video-based communication technology to deliver family therapy for treatment of perinatal depression in rural regions of the United States. The studies that have been conducted on this method of delivery focus on family therapy interventions for behavioral problems in children [41-44], but none have targeted perinatal depressive symptoms in young mothers with family discord [45]. The video-delivered family therapy intervention presented in this study is unique in that it addresses individual-level and family-level cognitive, emotion, and behavior regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a scarcity of research on the use of HIPAA-compliant video-based communication technology to deliver family therapy for treatment of perinatal depression in rural regions of the United States. The studies that have been conducted on this method of delivery focus on family therapy interventions for behavioral problems in children [41-44], but none have targeted perinatal depressive symptoms in young mothers with family discord [45]. The video-delivered family therapy intervention presented in this study is unique in that it addresses individual-level and family-level cognitive, emotion, and behavior regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Health Insurance Portability and Accountability Act (HIPAA)–compliant video-based communication technology is not novel in rural areas and ample evidence supports its use (eg, [39,40]). Studies have been conducted on video-delivered family interventions for some populations [41-44], but none have targeted perinatal depressive symptoms in home visited mothers [45].…”
Section: Introductionmentioning
confidence: 99%
“…Possible approaches that merit further exploration include: (i) considering how to adapt current practice to make it more family-friendly (eg, by identifying acceptable ways to include partners/relatives more meaningfully in (at least some) appointments), (ii) challenging the way service structures currently deprioritise family members’ needs, but also balancing this with protecting women’s needs, (iii) developing or adapting couple or family-focused interventions for perinatal populations: previous reviews suggest that family therapy can help address and prevent perinatal depression,29 30 and that couple psychoeducation can support the transition to parenthood 31. In England, clinical guidelines recommend couple or family approaches for some perinatal mental health difficulties,14 but such interventions are rarely available and have not been extensively tested in the perinatal period22, (iv) developing and testing resources/interventions aimed at women’s partners and wider families, acknowledging that some will themselves also have perinatal mental health needs: this will need to take into account that some family members express a preference for more ‘informal’ or ‘incidental’ forms of support (though this also may be partly a result of services treating them as ancillary) and (v) trialling specific staff training around engaging with families in the perinatal period, including awareness of cultural diversity.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is family interventions. A recent systematic review found two small treatment trials of couple interventions which were associated with improvements in maternal depressive symptoms 167 . As with research into maternal interventions, a core outcome set would be useful to improve methodological rigour.…”
Section: Interventionsmentioning
confidence: 99%